Metacognitive therapy for depression - Roger Hagen; Leif Edward Ottesen Kennair (Cogent Mental Health)
Depression is one of the most common psychiatric disorders and frequently accompanied by other mental disorders. There is therefore a need to develop and document new treatments that could have a beneficial effect in treating depression. A new treatment approach to depression that has produced encouraging results is metacognitive therapy (MCT). This paper provides a general introduction to the theory of MCT and especially of how to use MCT in treating depressive disorders. The treatment is illustrated with the clinical case of Andrew, and in the final part of this paper the current evidence for MCT for depression is presented.